2022
DOI: 10.7717/peerj.14375
|View full text |Cite
|
Sign up to set email alerts
|

High density and successful breeding of Turtle doves Streptopelia turtur in Moroccan olive groves

Abstract: Background The turtle dove is a migratory species that has suffered a rapid decline principally across its Northern ranges, despite pronounced conservation measures. Consequently, it has been categorized as ‘Near Threatened’ in Europe. Degradation of breeding habitats and a decrease in food resources are listed as principal causes of this decline. Despite its importance, the productivity of the North African population is widely unknown. Here we present the first estimation of the density of the breeding popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…during the nesting, laying, and incubation of chicks. This approach was used by Mansouri et al (Mansouri et al 2021b) and Squalli et al (Squalli et al 2022d) to evaluate the breeding success and failure factors during each breeding phase, which is impossible with methods that use the number of fledglings for nests. In parallel, we documented human and natural factors suggested to influence the breeding success of the studied species.…”
Section: Rates Of Breeding Successmentioning
confidence: 99%
See 3 more Smart Citations
“…during the nesting, laying, and incubation of chicks. This approach was used by Mansouri et al (Mansouri et al 2021b) and Squalli et al (Squalli et al 2022d) to evaluate the breeding success and failure factors during each breeding phase, which is impossible with methods that use the number of fledglings for nests. In parallel, we documented human and natural factors suggested to influence the breeding success of the studied species.…”
Section: Rates Of Breeding Successmentioning
confidence: 99%
“…have not yet been identified. Currently, cohabitation between avian species has received increasing attention, particularly in North African farmlands such as olive groves (Squalli et al 2022c;Squalli et al 2022d) and apple orchards (Mansouri et al 2022b). In our study, we demonstrated that the nests of cohabiting species were distributed differently among the monitored rivers.…”
Section: Discissionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before starting the statistical analysis, recorded species were grouped in orders and families as mentioned by [32,36,43]. Equally, the phenological status of breeding species (residents, breeders, migrants, and winterers) was noted based on the current phenology of Moroccan birds [45], while the conservation status of each breeding bird was cited following the latest IUCN Red list update [46]. Te number of breeding species and recorded nests were compared among nesting supports, including cavities and trees (exotic and natural plants) and urban breeding habitats via the one-way ANOVA test.…”
Section: Statisticsmentioning
confidence: 99%